Penerapan Metode Qawaid Wa Tarjamah Untuk Meningkatkan Pemahaman Struktur Bahasa Arab Dasar Mabni Dan Mu’rab - Surya Hidayat; Doni Sastrawan; Khairil Anwar (Al Mitsali, 2022)
This research is based on the low understanding of students in Arabic material, especially in mabni and mu'rab in the structure of Arabic. The method that the researchers used was "Application of the Qawaid Wa Tarjamah Method to Improve Understanding of the Basic Mabni and Mu'rab Arabic Language Structures". The formulation of the problem in this study is: can the application of the Qawaid Wa Tarjamah method increase the understanding of the basic Arabic language structures of mabni and mu'rab?. This research has been carried out in two cycles. Based on the implementation of this study using the Classroom Action Research (CAR) method which can help improve teacher teaching methods in the classroom, and can also be called a qualitative method. The average value of the pre test is 26.39. Researchers believe that this method is appropriate to apply. After being given this method, cycle I tests were carried out and an average value of 70.20 was obtained. There was an increase of 43.81 points. Then in the second cycle test obtained an average value of 80.90 points. Increased by 10.7 points from the cycle test. The increase in these two cycles was due to the maximum teaching techniques and the support of high student enthusiasm. From the results obtained from this study, it was concluded that the application of the Qawaid Wa Tarjamah method can improve understanding of the basic Arabic structure of Mabni and Mu'rab.